2018
DOI: 10.1016/j.celrep.2018.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Pathway Network, and Immunologic Features Distinguishing Squamous Carcinomas

Abstract: SUMMARY This integrated, multiplatform PanCancer Atlas study co-mapped and identified distinguishing molecular features of squamous cell carcinomas (SCCs) from five sites associated with smoking and/or human papillomavirus (HPV). SCCs harbor 3q, 5p, and other recurrent chromosomal copy-number alterations (CNAs), DNA mutations, and/or aberrant methylation of genes and microRNAs, which are correlated with the expression of multi-gene programs linked to squamous cell stemness, epithelial-to-mesenchymal differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
307
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(326 citation statements)
references
References 81 publications
17
307
0
2
Order By: Relevance
“…[8][9][10][11][12] However, more recent data demonstrated that both parameters do not or only marginally differ by HPV status. [13][14][15][16][17][18] This was especially apparent in data sets summarized by Hayes et al 17 and Campbell et al 18 including data of The Cancer Genome Atlas (TCGA). 15 These data sets clearly demonstrate that for the vast majority of the genome, the numbers of CNAs of HPV-positive and HPVnegative tumors are highly concordant with both groups showing fairly similar amplifications, especially at 1q, 3q, 5p, and 8q, and deletions at 3p, 5q, and 11q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] However, more recent data demonstrated that both parameters do not or only marginally differ by HPV status. [13][14][15][16][17][18] This was especially apparent in data sets summarized by Hayes et al 17 and Campbell et al 18 including data of The Cancer Genome Atlas (TCGA). 15 These data sets clearly demonstrate that for the vast majority of the genome, the numbers of CNAs of HPV-positive and HPVnegative tumors are highly concordant with both groups showing fairly similar amplifications, especially at 1q, 3q, 5p, and 8q, and deletions at 3p, 5q, and 11q.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that HPV‐positive HNSCC might have less copy‐number alterations (CNAs) and amplifications and also less mutations than HPV‐negative HNSCC . However, more recent data demonstrated that both parameters do not or only marginally differ by HPV status . This was especially apparent in data sets summarized by Hayes et al and Campbell et al including data of The Cancer Genome Atlas (TCGA) .…”
Section: Introductionmentioning
confidence: 99%
“…While shown to be critical in normal epidermal development and homeostasis, p63, particularly overexpression of the ΔNp63α isoform, is associated with squamous cancers including those of the head, neck, lung, and skin . Consistent with this, enriched ΔNp63 messenger RNA was recently identified in a PanCancer Atlas study as a molecular feature distinguishing squamous cell carcinomas across tissue sites including lung, head and neck, esophagus, cervix, and bladder from other cancers . Upon genomic analysis, metastatic cSCCs reportedly share molecular alterations similar to those in HNSCC, including enhanced expression of p63 and activation of NF‐κB signaling pathways .…”
Section: The P53/p63/p73 Family Of Transcription Factorsmentioning
confidence: 69%
“…It remains to be mechanistically determined whether similar mechanisms occur in other p63‐overexpressing cancers such as HNSCC and cSCC. Of note, the p63 gene is located on the long arm of chromosome 3 at position 28, and 3q28 amplification is a frequent early genomic event in the majority of HNSCCs …”
Section: Cross Talk Between the Nf‐κb And P63 Families Influences Thementioning
confidence: 99%
See 1 more Smart Citation